Stop rabies! maging responsableng amo sa alagang aso't pusa bdesigning a new brochure template for the zero rabies Philippines 2020 awareness campaign a print production thesis - Aguzar, Ed Ralph A.
Rabies is one of the most dangerous diseases in the world and is responsible for the deaths of 200-300 Filipinos yearly. The National government, with the help of the Department of Health (DOH) and Department of Agriculture Bureau of Animal Industry (DA-BAI) implemented the Zero Rabies Philippines 2020. This program aims to fight and eliminate rabies in the country. The said agencies used posters and used brochures to disseminate information about the campaign and its objective. However, the visual materials used were not designed for the campaign itself. This study was created to help DOH and DA-BAI in their combat against rabies. The objective of this thesis production is to design a brochure for information for Zero Rabies Philippines 2020. To achieve this objective, three creative processes were considered ? pre-production, production, and post-production. Information needed for the brochure was gathered on the pre-production phase. Conceptualizing on the brochure?s layout design using the elements and principles of visual design also took place in this phase. In the production phase, the researcher took and gathered photos that are needed and made a new brochure design for the campaign. Lastly, in the post-production phase, the researcher edited and made some enhancements on the design. At the end of this thesis production, the researcher was able to conclude that the principles and elements of visual design as well as the principles in photography is essential in creating an effective design that will help the Zero Philippines 2020 Awareness Campaign be successful in their fight against rabies.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts